Penerapan Metode Eksperimen Untuk Meningkatkan Aktivitas Siswa Pada Pembelajaran IPA Kelas V SD Negeri Ngemplak Kecamatan Windusari Kabupaten Magelang Provinsi Jawa Tengah - Mundiyah Mundiyah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The lack of student interest in learning science subjects due to the wide and varied scope of learning and the demands of a complete curriculum with content that must be delivered with a limited time allocation resulted in teachers having difficulty in developing learning methods according to student needs so that student learning outcomes were low. This study aims to increase students' learning motivation on the material for the Environment of Our Friends in class V SD Negeri Ngemplak by using the Experimental method in 2019/2020. The research was carried out in three cycles, with the object of research being 19th grade students, consisting of 10 girls and 9 boys. This research was conducted in three cycles, namely planning, action implementation, and reflection. Data collection techniques used are observation and tests. The application of the Experimental method has been proven to improve student achievement, courage, express opinions, and can learn through direct experience. Can enrich the experience with things that are objective and realistic, Can develop students' scientific attitude and can make learning actual.